Mapping system and services for canal operation techniques: the MASSCOTE approach - Renault, Daniel, author; Facon, Thierry, author; Wahaj, Robina, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
On the basis of previous tools and approaches widely used in Asia by the Food and Agriculture Organization (FAO) in its modernization program (Rapid Appraisal Procedure (RAP) & Benchmarking), FAO has developed a systematic approach for canal operation improvement from the diagnosis up to the formulation of operational units and planning of a service objective agreed upon with the users. The proposed comprehensive methodology for analyzing canal operation modernization, is based on a systematic mapping exercise: MApping System and Services for Canal Operation TEchniques — MASSCOTE (FAO, 2007). It consists of successively mapping: • Performance, through a Rapid Appraisal Procedure (RAP): to diagnose the processes and assess performance, increase knowledge about the constraints and opportunities which the system management has to consider. • System Capacity and Behaviour (Sensitivity): to assess the capacity of a canal network with regards to its various function (transport, diversion, control, etc.), as well as its behaviour through the sensitivity analysis. • Perturbations: which describes the disturbances (occurrences, magnitudes) that are likely to occur along the irrigation canal systems. • Water Networks and Water Balance: which influence the way water resources circulate, are managed and monitored. • Service to Users: to determine service objective characteristics tailored to the users' needs and willingness to pay. • Partitioning of Sub-Management Units: many large systems should be split into small (but not too small) manageable units. In the context of management transfer, users associations should be large enough to be able to recruit a professional to properly operate their sub-system. • Demand for Canal Operation, which depends on the service requirements, the perturbations, the opportunities for water management, and the capacity and sensitivity of the irrigation structures. • Options for Canal Operation Improvements, which are determined by the local conditions, availability of resources and capacity in mastering upgraded techniques. • Consolidation of a System Management Plan, with the goal to ensure consistency among the management units at the upper level. This paper describes the MASSCOTE methodology for developing a strategy for improvements in canal operation and the lessons learned from its application in several countries of Asia.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.